PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN PEMAIN BASKET PUTRA SMA NEGERI 1 TAMBANG - Teguh Krismon Jaya; Ardiah Juita; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine how much influence Fartlek training had on the Endurance of Men's Basketball Players at SMA Negeri 1 Tambang. This research was conducted at SMA Negeri 1 Tambang, Tambang District, Kampar Regency, in September 2021-November 2021. The population as well as samples in this study were students of SMA Negeri 1 Tambang, as many as 8 people. The data taken first was pretested by doing the Bleep test. Before doing Fartlek exercises on students of SMA Negeri 1 Tambang to find out the initial abilities of each student. test Based on the results of tcount of 2,371 with ttable of 1,895, ha is accepted, at the alpha level (0.05). It can be said that there is an effect of Fartlek Training on the Endurance of Men's Basketball Players at SMA Negeri 1 Tambang. Key Words: Effect of Fartlek Exercise, Basketball Player Endurance